Preparation for pre-ageing populations in the workplace: Spiritual health and psychological well-being development program - Chongvisal, Rattigorn (Kasetsart Journal of Social Sciences, 2021)
This study used action research to develop, implement, and evaluate a spiritual health and psychological well-being development program (SPDP) for preageing populations in the workplace. The results of the study were analyzed and used to develop a complete training curriculum and manual on spiritual health and psychological well-being development. The participants consisted of health care personnel in a hospital, educational personnel in an educational institution, and qualified experts who specialized in spiritual development. Both qualitative and quantitative methods were used to collect data. The research time frame was six months. The training curriculum and manual for the SPDP comprised four sets of training activities: (1) connection to self and a sense of self-worth, (2) connection to others (colleagues), (3) connection to society and the environment, and (4) planning of spiritual health and psychological well-being development in organizations. The quantitative data indicated that the participants’ spiritual health and psychological well-being significantly increased after joining the SPDP. According to the qualitative data analysis, the participants reported increased inner experiences, spiritual health, and psychological well-being after participating in the program. In addition, the qualitative data also indicated the development on spiritual health and psychological well-being development among the participants: impact on an inner experience of spiritual health development, psychological well-being development and achieving objectives of the training curriculum for the SPDP.